Modeling and simulation of queuing system to improve service quality at commercial bank of Ethiopia - Tamrat Yifter; Melkamu Mengstenew; Semehar Yoseph; Wongel Moges (Cogent Engineering, 2023)
AbstractThis study aims to develop a queuing model at the Commercial Bank of Ethiopia to improve the service quality perceived by customers using a simulation tool. Performance variables that were considered when developing this model are the average waiting time for a client to get service, customer arrival rates, and service time. After the identification of the problem, the service quality of the bank is assessed using a questionnaire that was prepared in SERVQUAL format. The filled-out and returned questionnaires were analyzed using SPSS, and the results show that the service quality of the bank was deemed very low. The recorded data was then ultimately used as a basis for the determination of arrival, service rates, and the distribution function in the simulation input analyzer. The distribution function determined was used as an input for the development of the existing queue model, and based on that, scientific scenarios are adopted from scientific research and further observations at the bank are added to show enhancement of the existing model. The study used four scenarios to test the response group, and one scenario was selected as the best. This has been identified by adding a server to the counters where there is less utilization, that is, servers four and five. As a result, the waiting time has been minimized by 20 minutes under server four and by 83.4 minutes under server five. Also, the number of customers served per day can be increased from 1048 to 1168, which is 11.45% improvement.